Efficacy of niclosamide as a potential antipenetrant (TAP) against cercariae of Schistosoma mansoni monkeys - John I. Bruce; Robert Miller; Lawrence Lightner; Subbiah Yoganathan (Memorias do Instituto Oswaldo Cruz, 1992)
A 1% (W/V) formulation of Niclosamide (2', 5-Dichloro-4-nitrosalicylanilide) (TAP) was tested on Cebus apella monkeys as a topical prophylatic against schistosomiasis mansoni. Two experiments were conducted using the same formulation. In the first experiment, the TAP provided complete protection against schistosomiasis for 3 days. Of the 4 monkeys treated with TAP 7 days before exposure to Schistosoma mansoni cercariae, 2 were completely protected. The remaining 2 monkeys of the 7 day treatment group had a 78% or greater reduction in adult worm buderns when compared to the placebo treated monkeys. The second experiment was designed determine the time between day 3 and 7 when the TAP no longer provided complete protection. However, all of the TAP treated monkeys in this experiment were completely protected, even the monkeys treated 7 days earlier. In both experiments, all monkeys used as infection controls and those receiving only the placebo became infected and showed typical experimental schistosomiasis. These results demonstrate that the TAP could provide fast acting, short-term protection to people who must enter cercariae infested water.